ANALISIS ITSM PADA LAYANAN SHOPEEFOOD BY SHOPEE DENGAN MENGGUNAKAN METODE COBIT 5 - Prasiska Adela Susilowati; Sri rahayu, Tata Sutabri (Jurnal Komunikasi, 2024)
Shopee Food is a platform that provides online food and beverage buying and selling transactions. This feature is officially part of Shopee e-commerce. With the presence of this feature, of course snack lovers have new options in addition to several large applications engaged in similar fields. Moreover, Shopee also provides the best offers for its users. need to manage IT Government to support academic and non-academic environment around customers and employees